PENERAPAN PEMASARAN DIGITAL BAGI UMKM DI ERA DIGITAL: LITERATURE REVIEW - Ceren Desta Joina; M.Irfansyah Afsalu Ramedhon; Sofiatun Anisa; Aqila, Reva Nur; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of information and communication technology has transformed marketing strategies, particularly for Micro, Small, and Medium Enterprises (MSMEs). Digital marketing has become an effective approach to improving competitiveness and expanding market reach in the digital era. This study aims to examine the implementation of digital marketing in MSMEs through a literature review. The research employs a literature review method by analyzing previous scientific studies related to digital marketing practices in MSMEs. The findings indicate that the use of social media, online marketplaces, WhatsApp Business, content marketing, and Search Engine Optimization (SEO) significantly enhances brand awareness, broadens market access, strengthens customer relationships, and increases sales performance and business sustainability. However, the implementation of digital marketing still faces several challenges, including limited digital literacy, inadequate human resources, insufficient technological infrastructure, and financial constraints. Therefore, continuous training, mentoring, and collaboration among the government, higher education institutions, and the private sector are essential to improve the digital capabilities of MSME owners. With proper implementation, digital marketing can become a strategic driver of digital transformation and sustainable business growth for MSMEs in the digital era.